The effect of the exchange rate system on economic growth of Bosnia and Herzegovina - Marjanac, Dražen (Anali Ekonomskog fakulteta u Subotici, 2020)
The subject of the research refers to the analysis of the influence of the exchange rate system in Bosnia and Herzegovina (BiH) on the macroeconomic indicators of economic growth. The goal of the research is to provide a theoretical and analytical overview of the mechanism of functioning and influence of the exchange rate system on inclusive economic growth in the long run. The research was conducted by applying the analysis of relevant literature, method of deduction and econometric calculations of the influence of the exchange rate system on macroeconomic indicators, that is, on gross domestic product, employment and trade balance. The research will offer an answer to the research question: Does the exchange rate system have an influence on the economic growth of Bosnia and Herzegovina in the long run? The results of the research will show the existence of the relation and influence of the exchange rate system on targeted macroeconomic parameters. Conclusions of the research relate to the confirmation of the basic hypothesis that the exchange rate of the convertible mark has bounded affect the growth of gross domestic product, employment and trade balance of Bosnia and Herzegovina in the long run. The contribution of the research is to present to the scientific and professional public the results of the analysis of the influence of the exchange rate system on economic growth, as well as possible alternatives and changes in the system that will enable faster and more stable economic growth in the long run.